The Significance of Reliability and Validity analysis on Education Supply Chain Management Practices - Basu Govindaraju; John Jeyasingam; Md. Mamun Habib; Uvarani Letchmana (International Journal of Supply Chain Management, 2019)
Abstract: Supply chain management practices (SCMP) have progressively emerged as a contingent factor in improving sustainable performance in universities. More and more organisations including the manufacturing and service sectors are making use of SCM to improve their performance. This study aims to develop an effective instrument to measure SCM practices with reliable predictors to enhance product quality and business performance in education industries in Malaysia. The study measures administrative staffs response and perceptions regarding SCM practices and its impact on performance in their universities. One hundred and thirty responses were received and the data was analysed using SPSS. The validity and reliability of the instruments used in determining SCM practices were tested using exploratory factor analysis (EFA) and Cronbachs alpha. Twenty seven items from five competencies comprising: supplier partnership, customer partnership, information sharing, information technology and innovation competencies were designated for the initial instrument. Exploratory factor analysis (EFA) revealed that five factor-structures of the instrument of education SCM practices explained 68.76% of the variance in the pattern of relationships among the items. All five factors had high reliabilities at or above of Cronbachs .80. Twenty two items remained in the final questionnaire after deleting five items which cross-loaded on multiple factors. The fiver-factor structure of the education SC practice instrument was confirmed through this study. Thus, practitioners may use such instruments in order to gain a better understanding of the level of contribution of the stated factors towards SCM practices to determine overall university performance and key competencies.